Eliminating Poverty and Inequality for Persons with Disabilities in Banda Aceh - Susrianti, Irna (H. : ĐHKT, 2020)
This research examines the root of poverty and inequality experienced by persons with disabilities (PwDs), discusses the changes in policy and perception on PwDs before and after 2004 Indian Ocean earthquake and tsunami and analyze the statutory coherence on the policy implementation. Determination of the sample is done by purposive sampling which is from the whole population was taken by several respondents and informants expected to represent the whole population. The location of the research is in Banda Aceh concerning the condition after tsunami disaster in 2004 that there were many international organizations came to this town and did disability rights advocacy to the government and society which is then expected has brought the changes in solidarity and accountability culture. Data have been collected from archives, interviews, Focus Group Discussions (FGDs) and published reports and articles. The research shows that the root of disability inequality started from inequality in opportunity that exclude majority of those people to access quality education and healthcare. Even though there is a change in disability right policy in Aceh, but it has not been fully implemented in the city level that leads to the difficulty of PwDs to access decent job and employment. Furthermore, the research finding is used in advocacy to challenge the local government in implementing inclusive employment that is affiliated with education, vocational training and human settlement by stressing dignity and inclusion in order to reach equality. The advocacy has led to the establishment inclusive employment policy which is stated in Banda Aceh Mayor Regulation No. 1 of 2019 concerning the fulfilment of the rights of persons with disabilities in obtaining decent work. Moreover, starting this year, women with disabilities are involved in development planning in Consensus of Action Female Plan in Banda Aceh.